THE DYNAMICS OF HIJRI MONTH DETERMINATION IN INDONESIA: RELIGIOUS AUTHORITY, PLURALISM, AND SOCIAL COHESION - Fauzi, Ahmad (Jurnal Al-Ijtimaiyyah, 2026)
The determination of the start of the Hijri month is a fundamental aspect of Islamic religious practice, particularly in setting the dates for religious observances such as Ramadan, Eid al-Fitr and Eid al-Adha. However, differences in determination methods and criteria often give rise to social dynamics within Muslim communities. This article aims to analyse the dynamics of determining the start of the Hijri month and its impact on the social cohesion of the Muslim community. This study employs a qualitative approach based on a literature review, analysing scholarly literature, institutional documents, and previous research through the framework of the sociology of religion, particularly theories of social cohesion and religious authority. The analysis focuses on how epistemological differences, the role of institutions, and socio-cultural contexts shape religious practices and social relations. The findings indicate that differences in Indonesia regarding the determination of the start of the Hijri month are influenced by variations in the interpretation of religious texts and astronomical criteria, as well as the authority of religious institutions. These differences have an ambivalent impact on social cohesion: they can trigger fragmentation, symbolic conflict, and polarisation, yet they also foster tolerance, pluralism, and mechanisms of social adaptation. This research contributes by shifting the focus of study from fiqh and astronomical approaches towards a sociological approach that places social cohesion at the centre of the analysis.